An investigation of natural cadence between cyclists and noncyclists - MacPherson, A. C.; Turner, A. P.; Collins, D. (Research Quarterly for Exercise and Sport, 2007)
The aim was to investigate whether there is a natiral cadence in cyclists. Also the authors loked at the physiological response postperturbation from fixed cadence t establish whether participants would revert to similar values , comparable with NC.